2017
DOI: 10.1186/s13012-017-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Organizational participatory research: a systematic mixed studies review exposing its extra benefits and the key factors associated with them

Abstract: BackgroundIn health, organizational participatory research (OPR) refers to health organization members participating in research decisions, with university researchers, throughout a study. This non-academic partner contribution to the research may take the form of consultation or co-construction. A drawback of OPR is that it requires more time from all those involved, compared to non-participatory research approaches; thus, understanding the added value of OPR, if any, is important. Thus, we sought to assess w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 44 publications
2
76
0
4
Order By: Relevance
“…In other words, the benefits of researcher and research user partnerships may not be realised if flourishing partnerships are not established at the outset. While previous reviews [9] and concept analyses [10,11,16,17] of researcher and research user partnerships have been published, none of those specifically assessed partnership initiation in depth. Bush et al [17] concluded that co-creation partnerships, that is, partnerships to co-create knowledge, initiated by research user organisations appear to have greater beneficial outcomes than consultative type partnerships initiated by either universities or research user organisations.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the benefits of researcher and research user partnerships may not be realised if flourishing partnerships are not established at the outset. While previous reviews [9] and concept analyses [10,11,16,17] of researcher and research user partnerships have been published, none of those specifically assessed partnership initiation in depth. Bush et al [17] concluded that co-creation partnerships, that is, partnerships to co-create knowledge, initiated by research user organisations appear to have greater beneficial outcomes than consultative type partnerships initiated by either universities or research user organisations.…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, the practice manager explained that practitioners were more aware of migrants' issues, but there had been no change in the actual practice during consultations (Ire10, 13,14). While the doctors knew that using a trained interpreter was the correct thing to do, they still did not have resources from the health service to do so.…”
Section: (Nl;pca)mentioning
confidence: 99%
“…This is in line with the review by Bush et al that revealed a range of positive yet unanticipated effects of participatory research projects. 13 That review also underscored the need for all partners to agree on the importance of the research focus. Even more importantly, the likelihood of a participatory project exhibiting at least one extra benefit is quadrupled when the impetus for the study comes from a community organization.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 2 more Smart Citations